Assessment of Dasatinib Versus Nilotinib as Upfront Therapy for Chronic Phase of Chronic Myeloid Leukemia in Qatar: A Cost-Effectiveness Analysis - Adel, Ahmad (Cancer Control, 2021)
BACKGROUND: The economic outcome research of approved tyrosine kinase inhibitors for treating the chronic phase of chronic myeloid leukemia in developing is scarce. The aim of this study was to assess the cost-effectiveness of dasatinib and nilotinib for newly diagnosed chronic myeloid leukemia patients. METHODS: A decision tree model was developed linking clinical effectiveness (defined as major molecular response) and/or complete cytogenetic response, utility, and cost data over a 12-month period. Patients are recruited from Qatar Cancer Registry. The probability of primary clinical outcome is calculated from DASISION (dasatinib) and ENESTnd (nilotinib) trials. Direct healthcare costs were derived from the national healthcare payer system, whereas adverse effects data were derived from local incident reporting system. RESULTS: In the first-line treatments of chronic myeloid leukemia patients, nilotinib has greater major molecular response (39% nilotinib vs 12% dasatinib) and complete cytogenetic response (24% nilotinib vs 16% dastinib) response outcomes, and more adverse effects than dasatinib (13.3% vs 4%). Moreover, nilotinib is more cost-effective with annual costs (USD63,589.59) and after 12 months of follow-up. Despite the lower acquisition annual cost of dasatinib (USD59,486.30), the incremental cost-effectiveness ratio of nilotinib (vs dasatinib) per major molecular response/complete cytogenetic response achieved was USD15,481.10 per year. There were no cases in both arms that progressed to accelerated or blast phase. At a threshold of 3 times gross domestic product per capita of Qatar and according to World Health Organization recommendation, the nilotinib use is still cost-effective. CONCLUSION: Upfront therapy of chronic myeloid leukemia–chronic phase patients by nilotinib plan appears to be more cost-effective than dasatinib.